Association of lung function decline with the heme oxygenase-1 gene promoter microsatellite polymorphism in a general population sample. Results from the European Community Respiratory Health Survey (ECRHS), France. Issue 8 (1st August 2006) - Guénégou, A; Leynaert, B; Bénessiano, J; Pin, I; Demoly, P; Neukirch, F; Boczkowski, J; Aubier, M
Abstract : Inducible heme oxygenase (HO-1) acts against oxidants that are thought to play a major role in the pathogenesis of chronic obstructive pulmonary disease (COPD), characterised by impaired lung function. A (GT)n repeat polymorphism in the HO-1 gene promoter can modulate the gene transcription in response to oxidative stress. We hypothesised that this polymorphism could be associated with the level of lung function and decline in subjects exposed to oxidative agression (smokers). We genotyped 749 French subjects (20–44 years, 50% men, 40% never smokers) examined in both 1992 and 2000 as part of the ECRHS. Lung function was assessed by forced expiratory volume in 1 second (FEV1 ) and FEV1 /forced ventilatory capacity (FVC) ratio. We compared long (L) allele carriers ((GT)n ⩾33 repeats for one or two alleles) to non-carriers. Cross sectionally, in 2000, L allele carriers showed lower FEV1 /FVC than non-carriers. During the 8 year period, the mean annual FEV1 and FEV1 /FVC declines were −30.9 (31.1) ml/year and −1.8 (6.1) U/year, respectively. FEV1 /FVC decline was steeper in L allele carriers than in non-carriers (−2.6 (5.5) v −1.5 (6.4), p = 0.07). There was a strong interaction between the L allele and smoking. In 2000, the L allele was associated with lower FEV1 and FEV1 /FVC in heavy smokers (⩾20 cigarettes/day) only (p for interaction = 0.07 and 0.002 respectively). Baseline heavy smokers carrying the L allele showed the steepest FEV1 decline (−62.0 (29.5 ml/year) and the steepest FEV1 /FVC decline (−8.8 (5.4 U/year) (p for interaction = 0.009 and 0.0006).These results suggest that a long (L) HO-1 gene promoter in heavy smokers is associated with susceptibility to develop airway obstruction.